Larisa Vasilyevna Rudchenko - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 80th anniversary of the birthday of a employee of pediatric orthopaedics clinic of Sytenko Institute of Spine and Joint Pathology of the National Academy of Medical Sciences of Ukraine, pediatric orthopaedist-traumatologist, doctor of higher category candidate of medical science Rudchenko L. V.